Blockchain Disaster Management for Humanitarian Logistic as Post-Disaster Response Measures - Mohamad Faherza Hasyir Rahman; Ihsan Nurhadi; Sheren Aurelia Widjaja; Tobi Anggesta; Putri Anjar Sari; Zeqy Zulhaqy; Hanissa Okitasari (Journal of Logistics and Supply Chain, 2023)
Indonesia has a high risk of earthquake and tsunami disasters because there's many tectonic plates meet. This also causes Indonesia to have many geological changes compared to other countries. Therefore, an explicit scheme to provide information related to disasters, like an information system in post-disaster management is important. The purpose of this research is to provide transparent information regarding the data on the goods needed and the data on goods to be distributed to ensure the amount used and not used, so that victims affected by disasters can be handled quickly and appropriately. The method used in this research is a literature review. The results of this study indicate the existence of a Blockchain Disaster Management Information System as a form of a new scheme in the post-disaster management process and is an upgraded form of information system that has been developed previously. This scheme uses the blockchain concept to provide transparency and data immutability. This scheme coordinates with various institutions such as BPBD (Regional Disaster Management Agency), BNPB (National Disaster Management Agency), BASARNAS (National Search and Rescue Agency), PMI (Indonesian Red Cross Society), the nearest hospital, and other related institutions.  © 2023 Universitas Pendidikan Indonesia